In vivo imaging with a water immersion objective affects brain temperature, blood flow and oxygenation - Morgane Roche; Emmanuelle Chaigneau; Ravi L Rungta; Davide Boido; Bruno Weber; Serge Charpak (eLife, 2019)
Previously, we reported the first oxygen partial pressure (Po2) measurements in the brain of awake mice, by performing two-photon phosphorescence lifetime microscopy at micrometer resolution (Lyons et al., 2016). However, this study disregarded that imaging through a cranial window lowers brain temperature, an effect capable of affecting cerebral blood flow, the properties of the oxygen sensors and thus Po2 measurements. Here, we show that in awake mice chronically implanted with a glass window over a craniotomy or a thinned-skull surface, the postsurgical decrease of brain temperature recovers within a few days. However, upon imaging with a water immersion objective at room temperature, brain temperature decreases by ~2–3°C, causing drops in resting capillary blood flow, capillary Po2, hemoglobin saturation, and tissue Po2. These adverse effects are corrected by heating the immersion objective or avoided by imaging through a dry air objective, thereby revealing the physiological values of brain oxygenation.